Case of Amorphous globosus in a Kyrgyz mare - Risvanli, A.; Yildirim, S.; Abdimanap Uulu, N.; Belek Kyzy, S.; Zhumagulov, I.; Kirtay, S.; Toprak, E. (Wiley, 2026)
This case report presents a case of Amorphous globosus detected in an 8-year-old Kyrgyz mare brought to the Obstetrics and Gynaecology Clinic of the Veterinary Faculty at Kyrgyzstan-Turkey Manas University. The mare was brought to the clinic because she had not given birth despite being 1 month past her expected delivery date. Examinations revealed uterine rupture and an abnormal tissue mass associated with the fetus in the abdominal cavity. During necropsy, an intact foal was observed, along with an independent tissue mass measuring approximately 30 & times; 40 cm, covered with skin and containing intestinal tissues. Histopathological examination revealed intense autolysis in this tissue, fibrosis in the dermis and oedema in the intestinal serosa; the structure was defined as A. globosus. This anomaly, rarely reported in mares in the literature, is generally defined as an acardiac, skin-covered, asymmetric mass resulting from twin pregnancy. This case differs from other cases in the literature in that it is the first report in a Kyrgyz mare and that the A. globosus disintegrated in the uterus and fell into the abdominal cavity.
Keywords: horse; Amorphous globosus; Kyrgyz; mare